Hubungan Intensitas Kebisingan Dengan Penurunan Daya Dengar Tenaga Kerja Bagian Produksi Di Pt Wijaya Karya Beton Tbk PPB Majalengka - Rahmawati, Fitri Nur (2016)
Noise is one of the physical factors such as noise that can lead to bad consequences for health and safety . In an industrial activity , exposure and risk of danger in the workplace can not always be avoided . Therefore we need a comfortable working environment in order to avoid noise workforce . The aim of this study was to determine the relationship of the intensity of noise with reduced hearing labor in production PT Wijaya Karya Beton Tbk PPB Majalengka. This research uses an observational analytic approach cross sectional. Sampling techniques using methods purposive sampling with a sample of 30 respondents. Analysis of data using statistical tests chi-square with a significant level α = 0.05 using SPSS. The results showed that there is a significant correlation between the intensity of noise with reduced hearing ( p =0,028) (p < 0,05).